2011
DOI: 10.5588/ijtld.10.0564
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among household contacts of multidrug-resistant tuberculosis patients in Delhi, India

Abstract: The majority of contacts of MDR-TB patients had drug-susceptible TB and the rate of MDRTB was very low. Evaluation of contacts of MDR-TB cases may lead to early diagnosis and prevention of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 2 publications
4
18
0
1
Order By: Relevance
“…41 We found only one resistant case (1.02%) with history of contact with MDR TB. This is consistent with a study done by N Singla et al 42 in which only 0.66% of contacts developed MDR TB. Three patients (3.06%) among rifampicin resistant cases were found to be HIV seropositive.…”
Section: Discussionsupporting
confidence: 93%
“…41 We found only one resistant case (1.02%) with history of contact with MDR TB. This is consistent with a study done by N Singla et al 42 in which only 0.66% of contacts developed MDR TB. Three patients (3.06%) among rifampicin resistant cases were found to be HIV seropositive.…”
Section: Discussionsupporting
confidence: 93%
“…Although adolescents may be able to more easily provide sputum samples for diagnosis when compared with children, they may be less likely to follow up on referrals [32]. A potential strategy for earlier diagnosis is active screening and immediate clinical referral of all household contacts of persons with MDR-TB [33], given that more than one-third of the adolescents in this study had a known MDR-TB contact; had they been identified through an active case-finding strategy, perhaps they would have been diagnosed more quickly and benefitted from earlier treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Spread of MDR-TB among household contacts of MDR-TB patients is well documented with a prevalence of MDR-TB in contacts ranging between 1.8% and 11.2% [2]–[11]. Also, MDR-TB outbreaks within health care facilities [12], schools [13], work places [14] and other confined settings [15] have been reported.…”
Section: Introductionmentioning
confidence: 99%